Articulation of Islamic Political Parties in The Constellation of National Politics Post Democratic Transition - Busman Edyar; Ilda Hayati (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research aims to examine the articulation of Islamic political parties post democratic transition. This is a literature study with an empirical sociological approach which is analyzed by means of content analysis. The results of the research show that Islamic political parties during the post democratic transition have fluctuated; however, they have never moved from the middle class. In the last five elections, it can be seen that Islamic political parties have stagnated (and even seems to decline) and are difficult to grow and develop. There are several contributing factors; first, the increasing number of Islamic political parties has caused the concentration of Muslims to break into many Islamic political parties. Second, the increasingly diluted political orientation of Muslims towards Islamic political parties. The secularization of politics that had occurred during the new order had contributed to the changing of political orientation of Muslims who no longer identified the party with Islam; third, the failure of Islamic political parties to show themselves as parties that have a distinctive difference compared to other nationalist political parties both related to political behavior or image and work programs; fourth, the shrewdness of nationalist parties in approaching Muslims by establishing wing organizations in each party; and the last one, the internal conflicts of Islamic political party elites that make constituents become apathetic about the future of these political parties.